Implementasi Manajemen Risiko Pada Account Receivable Di The Westin Resort & Spa Ubud Bali - Pande Komang Feby Wahyuni; I Putu Arnawa; Ni Made Sri Rukmiyati (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the implementation of risk management in accounts receivable at The Westin Resort & Spa Ubud Bali. Accounts receivable is a crucial component in maintaining the smooth cash flow of the hotel, but it is also highly vulnerable to the risk of bad debts, which can impact the company's financial stability. In daily operations, bad debts, especially from third parties such as travel agents, are one of the main challenges faced by the hotel's finance team. This study uses a qualitative descriptive approach with data collection methods through in-depth interviews with account receivable staff and analysis of documents and accounts receivable reports for 2023–2024. The results show that the hotel has implemented five main stages in the risk management process: risk identification, risk analysis, risk evaluation, risk control, and risk monitoring. The main risks identified are bad debts due to late or inability to pay from travel agents and human error in the administrative process. Technology-based monitoring systems such as Opera System have been used to monitor and record accounts receivable activities routinely. However, this study also identified several weaknesses, such as a lack of formal documentation related to identified risks and a reactive rather than proactive risk management strategy. In conclusion, the implementation of risk management in accounts receivable at The Westin Resort & Spa Ubud Bali has been quite successful. However, improvements are still needed in terms of risk recording, strengthening the documentation system, and providing regular training to relevant staff. With these improvements, accounts receivable management can be more effective and contribute positively to the hotel's overall financial sustainability.